Secondary Syphilis During Pregnancy: The Importance of Screening and Clinical Management - Purnamasari, Indah; Barakbah, Jusuf; Martodiharjo, Sunarko; Murtiastutik, Dwi; Astindari, Astindari; Septiana, Septiana; Sari, Maylita; Hidayati, Afif Nurul (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Syphilis is one of the most serious sexually transmitted diseases worldwide, and has tremendous consequences for the mother and her developing fetus if left untreated. The burden of morbidity and mortality due to congenital syphilis is high. Purpose: Screening and prompt to know the importance of treatment of syphilis during pregnancy. Case: A 32-year-old multigravida in 5 months of pregnancy presented with multiple raised lesions over her labia. It was accompanied by fluor and smelly fishy odor. There was no history of genital ulcers in either spouse and no history of sexual promiscuity. History of antenatal care in public health showed non-reactive status of HIV, syphilis and hepatitis B. Clinical examination revealed multiple flat, moist warts over her labia mayora and minora, and multiple roseola syphilitica on the plantar pedis sinistra. Darkfield microscopic examination presence spirochete, venereal disease research laboratory (VDRL) titer was 1:16 and T. pallidum particle agglutination assay (TPHA) titer was 1:2560. Obstetric ultrasonography examination was suggestive no mayor congenital abnormalities. Both of serology VDRL and TPHA were non-reactive in her husband. Significant of lesion improvement and decrease a fourfold titer serologic in VDRL (1:4) and TPHA (1:320) as follow-up 3 months after being treated with single intra-muscular injections of benzathine penicillin 2.4 million units. Discussion: Coordinated prenatal care and treatment are vital. It's implemented before the fourth month of pregnancy to reduce vertical transmission and all associated side effects of congenital syphilis. Penicillin is highly efficacious in maternal syphilis and prevention of congenital syphilis. Conclusion: Universal screening and adequate pregnancy care must be a priority.